2020
DOI: 10.3390/ph13050093
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-Induced Killer (CIK) Cells, In Vitro Expanded under Good Manufacturing Process (GMP) Conditions, Remain Stable over Time after Cryopreservation

Abstract: Cytokine-induced killer (CIK) cells are advanced therapy medicinal products, so their production and freezing process has to be validated before their clinical use, to verify their stability as a drug formulation according to the good manufacturing practice (GMP) guidelines. We designed a stability program for our GMP-manufactured CIK cells, evaluating the viability, identity and potency of cryopreserved CIK cells at varying time periods from freezing, and compared them with fresh CIK cells. We evaluated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…As expected, reductions of both recovery rate and functionality were detectable compared to stable gas phase storage, however, only when the number of cycles exceeded 20 and/or the peak temperature was higher than -100°C, thus indicating that cell damage develops only after several temperature transition cycles. Recently, Mareschi et al compared the post-thawing viability of cytokine-induced killer cells stored in dry ice for 24 or 48 h or in LN 2 vapours (27). Because cell viability between the two groups was comparable (acceptance criteria was 15%), the authors concluded that these cells could be shipped safely in dry ice (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, reductions of both recovery rate and functionality were detectable compared to stable gas phase storage, however, only when the number of cycles exceeded 20 and/or the peak temperature was higher than -100°C, thus indicating that cell damage develops only after several temperature transition cycles. Recently, Mareschi et al compared the post-thawing viability of cytokine-induced killer cells stored in dry ice for 24 or 48 h or in LN 2 vapours (27). Because cell viability between the two groups was comparable (acceptance criteria was 15%), the authors concluded that these cells could be shipped safely in dry ice (27).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Mareschi et al compared the post-thawing viability of cytokine-induced killer cells stored in dry ice for 24 or 48 h or in LN 2 vapours (27). Because cell viability between the two groups was comparable (acceptance criteria was 15%), the authors concluded that these cells could be shipped safely in dry ice (27).…”
Section: Discussionmentioning
confidence: 99%
“…We had no data regarding the potential effects that cell transitions from LN 2 to dry ice and then to 37 °C could have on cell efficacy and safety. The literature concerning the effects of temperature fluctuations of frozen product during sample transfer from LN 2 to dry ice was limited [23][24][25][26], so we conducted an internal validation process. Chabot et al showed that warming of UC-MSCs from LN 2 to approximately − 80 °C does not have a major impact on MSCs, while internal vial temperatures higher than − 40 °C significantly impair their antiproliferative effects vs. T-cells, and degrade membranous and cytoskeletal integrity [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Mareschi et al compared the post-thawing viability of cytokine-induced killer cells stored in dry ice for 24 or 48 h or in LN 2 vapours [26]. Because cell viability between the two groups was comparable (acceptance criteria was 15%), the authors concluded that these cells could be shipped safely in dry ice [26]. Under Good Clinical Practice regulations, shipping conditions must also be validated to ensure that the temperature of the product is kept constant during transportation, and that the quantity of refrigerant is sufficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation